2019
DOI: 10.31742/ijgpb.79s.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Genomics-assisted backcross breeding for infusing climate resilience in high-yielding green revolution varieties of rice

Abstract: Rice is the most important food crop both in value and volume for the Asian population. Frequent drought, flood and salinity stresses exacerbated by global climate change adversely affect rice production in more than fifty percent of the rice growing areas. Green revolution high yielding varieties carrying sd1 dwarfing gene have almost fully replaced the traditional climate resilient landraces and varieties of rice. However, these were bred primarily for yield under high input conditions and therefore are sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…We targeted four QTLs— qDTY1.1, qDTY2.1, qDTY3.1 and qDTY12.1 —for reproductive-stage drought tolerance. In previous studies, the introgression of these four QTLs in different combination along with Sub1 for submergence tolerance resulted in development and release of drought- and submergence-tolerant versions of mega varieties like Swarna as CR dhan 801 ( qDTY1.1 +qDTY2.1 +qDTY3.1 +Sub1 ) and CR Dhan 802 ( qDTY2.1+qDTY3.1+Sub1 ) and Samba Mahsuri as DRR Dhan 50 ( qDTY2.1+qDTY3.1+Sub1 ) as new cultivars in various rice growing countries of Southern Asia [ 41 , 51 , 52 , 53 ]. In the present study, we identified five ILs viz., IL 19,196 with Xa21+Pi9+qDTY3.1 , ILs 19,174 and 19,193 with xa5+Xa21+qDTY3.1 and ILs 19,246 and 19,247 with qDTY2.1 introgressions and yield advantage of 131 to 346 g/m 2 under reproductive-stage drought stress over Krishna Hamsa, accounting to a percentage yield advantage of 68%–180% along with BB and blast resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We targeted four QTLs— qDTY1.1, qDTY2.1, qDTY3.1 and qDTY12.1 —for reproductive-stage drought tolerance. In previous studies, the introgression of these four QTLs in different combination along with Sub1 for submergence tolerance resulted in development and release of drought- and submergence-tolerant versions of mega varieties like Swarna as CR dhan 801 ( qDTY1.1 +qDTY2.1 +qDTY3.1 +Sub1 ) and CR Dhan 802 ( qDTY2.1+qDTY3.1+Sub1 ) and Samba Mahsuri as DRR Dhan 50 ( qDTY2.1+qDTY3.1+Sub1 ) as new cultivars in various rice growing countries of Southern Asia [ 41 , 51 , 52 , 53 ]. In the present study, we identified five ILs viz., IL 19,196 with Xa21+Pi9+qDTY3.1 , ILs 19,174 and 19,193 with xa5+Xa21+qDTY3.1 and ILs 19,246 and 19,247 with qDTY2.1 introgressions and yield advantage of 131 to 346 g/m 2 under reproductive-stage drought stress over Krishna Hamsa, accounting to a percentage yield advantage of 68%–180% along with BB and blast resistance.…”
Section: Discussionmentioning
confidence: 99%
“…MAB also permits restricting the donor region thereby eluding linkage drag [ 148 ]. Marker-assisted breeding (MAB) was fortunate in the development of salinity tolerance lines in rice [ 148 , 149 , 154 – 158 ]. In rice, marker-assisted breeding has been utilized in pyramiding of QTLs which control tolerance against salinity, submergence, as well as drought [ 6 ].…”
Section: Main Textmentioning
confidence: 99%
“…The identification and introgression of the trait (s)/genomic regions of interest are the well-known approaches for the development of salinity tolerant varieties [93,94]. Marker assisted breeding approaches have been proven successful in developing new improved, high yielding salt tolerance rice varieties [95][96][97][98][99][100].…”
Section: Salinitymentioning
confidence: 99%